2007
DOI: 10.1002/dvg.20297
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of the mouse Slc39a2 (Zip2) gene reveals highly cell‐specific patterns of expression, and unique functions in zinc, iron, and calcium homeostasis

Abstract: Fourteen members of the Slc39a superfamily of metal ion uptake transporters have been identified in mice and humans, but the physiological functions of most remain obscure. Herein, we created mice with Zip2 (Slc39a2) genes in which the open reading frame was replaced with that of the enhanced green fluorescent protein (EGFP), to study temporal and spatial patterns of Zip2 gene expression and examine the physiological roles of this transporter. Expression of this gene was remarkably cell-type specific and devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 61 publications
3
52
0
Order By: Relevance
“…Scale bars ϭ 50 m. knockout mice exhibit skin blistering during early embryogenesis. However, the underlying mechanism for this remains unknown (24). Considering the results of our study, it is likely that Zip2 knockout mice developed a deficiency in the skin because of the abnormal differentiation of keratinocytes.…”
Section: Discussionmentioning
confidence: 74%
“…Scale bars ϭ 50 m. knockout mice exhibit skin blistering during early embryogenesis. However, the underlying mechanism for this remains unknown (24). Considering the results of our study, it is likely that Zip2 knockout mice developed a deficiency in the skin because of the abnormal differentiation of keratinocytes.…”
Section: Discussionmentioning
confidence: 74%
“…In initial screens of the remaining 12 ZIP family members, we have evidence that only one of these, ZIP2, appears capable of transporting iron. 3 Interestingly, previous studies of the Zip2 knock-out mouse concluded that ZIP2 plays a role in iron homeostasis (53). In an effort to identify which of the 14 ZIP family members might transport iron, we previously examined the effect of iron deficiency and iron overload on the expression of all the ZIP proteins in rat liver (22).…”
Section: Discussionmentioning
confidence: 99%
“…Chelex-treated FBS was filter sterilized, aliquoted, and stored at Ϫ80°C. Metal concentrations were measured by inductively coupled plasma mass spectrometry (7,21). DMEM or DMEM/F-12 was adjusted to 10% or 5%, respectively, with Chelex-treated FBS, which restored all the essential metals to near normal concentrations except for zinc, which was reduced about 100-fold.…”
Section: Methodsmentioning
confidence: 99%